2021
DOI: 10.1002/jlb.3ma0321-739r
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained calcium ion release from bioceramics promotes CaSR-mediated M2 macrophage polarization for osteoinduction

Abstract: Innate immune cells, especially macrophages, play a dual role in tissue repair and the defense against foreign bodies. Although biphasic calcium phosphate (BCP) ceramics have been confirmed as an excellent osteoimmunoregulatory biomaterial, it is unclear whether the ions release of BCP directly affects macrophage polarization and the mechanism by which the ions release is involved in osteoimmunomodulation. Herein, we verified the superior osteoinductive capacity of BCP in wild‐type mice and showed its inabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
(66 reference statements)
4
41
0
Order By: Relevance
“…Of the ions PMCs release, calcium has the strongest correlation with new bone formation in vivo and is one of the most clearly understood mechanisms underlying direct effects ( Table 4 ), via the calcium sensing receptor (CSR). These studies in Table 4 show that increases in bone formation in vivo are correlated with chronic calcium release in the range of 0.5–20 mM [ 49 , 50 , 51 , 52 , 53 , 54 ]. Excessive calcium is cytotoxic in vitro above 10 mM [ 55 ], but little information is available on the local cytotoxicity, or inhibitory dosage, in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the ions PMCs release, calcium has the strongest correlation with new bone formation in vivo and is one of the most clearly understood mechanisms underlying direct effects ( Table 4 ), via the calcium sensing receptor (CSR). These studies in Table 4 show that increases in bone formation in vivo are correlated with chronic calcium release in the range of 0.5–20 mM [ 49 , 50 , 51 , 52 , 53 , 54 ]. Excessive calcium is cytotoxic in vitro above 10 mM [ 55 ], but little information is available on the local cytotoxicity, or inhibitory dosage, in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium release from PMCs can be finely tuned by altering the composition (e.g., add more calcium salt, or a more basic calcium salt to alter the pH) and setting conditions. When comparing the chronic release rate of calcium between PMCs and other biomaterials, prefabricated ion-coated polymers release 0.2 mM [ 56 , 61 ] to 2 mM [ 50 ], bioglass (BG45S5) releases 33 mM [ 62 ], sintered hydroxyapatite discs and scaffolds release 0.05–0.25 mM [ 51 , 52 , 54 , 57 , 63 , 64 ], and tricalcium phosphates release 0.1–2.5 mM of calcium each day. In short, fluids incubated with fully cured PMCs contained 1–20 fold more (soluble) calcium than “osteoinductive calcium” phosphate bioceramics, up to half as much as osteoinductive polymer composites, and 30-fold less calcium than bioglass when the media were replenished frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that Ca 2+ ions released from CaP bioceramics contribute to modulate the biological behavior of macrophages [ [54] , [55] , [56] ]. Continuous release of Ca 2+ ions from CaP bioceramics activates the Wnt/β-catenin pathway in macrophages through the calcium-sensitive receptor CaSR, thus promoting the M2 macrophages [ 56 ]. Another study also shows that Ca 2+ ions are involved in the regulatory effect of CaP bioceraics on macrophage polarization via upregulating IκBα [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also shows that Ca 2+ ions are involved in the regulatory effect of CaP bioceraics on macrophage polarization via upregulating IκBα [ 37 ]. Ca 2+ ion concentration varies in CaP bioceramics, leading to distinct macrophage phenotypes [ 37 , 56 ]. Actually, our study focused on the similar topic with previous findings, but a new perspective was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the intermediate macropore size (20–400 μm) of ceramic was associated with low resorption and excellent bone formation [ 30 ]. Low resorption of ceramic scaffold could release sustained calcium ion and trigger CaSR signal pathway [ 31 ]. This may explain, at least in part, the osteo-inductive capability of the BCP synthesized in this study.…”
Section: Discussionmentioning
confidence: 99%